Development of a numerical model for performance-based design of geosynthetic liner systems. Issue 2 (April 2018) - Kavazanjian, E.; Wu, X.; Arab, M.; Matasovic, N.
Abstract: A numerical model for performance-based design of the geosynthetic elements of waste containment systems has been developed. The model offers a rational alternative to the current state of practice for design of geosynthetic containment system elements in which neither the strains nor the forces in liner system elements are explicitly calculated. To explicitly assess the ability of the geosynthetic elements of a containment system to maintain their integrity under both static and seismic loads, a large strain finite difference model of waste-liner system interaction was developed. Modular features within the model allow the user to select the appropriate features required for any particular problem. A beam element with zero moment of inertia and with interface elements on both sides is employed in the model to represent a geosynthetic element in the liner system. This enables explicit calculation of the axial forces and strains within the liner system element. Non-linear constitutive models were developed to represent the stress-strain behavior of geomembrane and geosynthetic clay liner beam elements and the load-displacement behavior of the beam interfaces. The use of the various features on the model is illustrated using available experimental data, including shaking table test data on rigid and compliant blocks sliding on geomembranes. Analysis of geomembranes subject to waste settlement and subject to seismic loading demonstrate applications of the model and provide insight into the behavior of geosynthetic liner system elements subject to tensile loads.